Peran Tiktok Live dalam Meningkatkan Engagement pada Akun @hitabalikebaya - I Gusti Agung Ayu Vanya Belinda Putri Biantara; Ni Putu Yunita Anggreswari; Jonathan Jacob Paul Latupeirissa; I Nyoman Indra Kumara (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of social media has encouraged brands to utilize various digital features not only to promote their products but also to build interaction with their audiences. One of the most widely used features is TikTok Live, as it enables real-time two-way communication between brands and audiences. This study aims to examine the use of TikTok Live on the @hitabalikebaya account in increasing audience engagement. This research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The informants in this study consist of the business owner, live hosts, and several audience members who have watched TikTok Live sessions on the account.This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The informants in this study consisted of the owner, live host, and several audiences who had watched TikTok Live on the account. The results show that TikTok Live functions as both a promotional medium and an interactive communication platform, allowing audiences to actively participate through comments and responses during the live sessions. This interaction is able to increase audience engagement, as reflected in activities such as giving likes, commenting, sharing the live stream, and following the account after watching. Based on the analysis using The Circular Model of Social Media Engagement (SoMe), the implementation of TikTok Live on the @hitabalikebaya account reflects the stages of share, optimize, manage, and engage in building audience engagement. Therefore, TikTok Live also serves as a medium for building closer and more sustainable relationships between brands and audiences.